Implementation of IoT-Based Facial Recognition for Home Security System Using Raspberry Pi and Mobile Application - Sarimole, Frencis Matheos; Septianto, Ahas Eko (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
The rapid advancement of technologies such as Artificial Intelligence (AI), computer vision, and the Internet of Things (IoT) has significantly impacted various fields, particularly in security systems. Traditional security measures, such as door locks, are increasingly inadequate in ensuring the safety of homes. To address this issue, we have developed a prototype of a home security system based on Raspberry Pi, integrated with a real-time mobile application. This intelligent system is designed to monitor residential areas, detect unfamiliar individuals, and send immediate notifications to the homeowner's mobile device. Utilizing Raspberry Pi in conjunction with OpenCV for motion and facial recognition, as well as a web server, the system demonstrates high accuracy in detecting motion and faces. It promptly notifies the homeowner in the event of suspicious activity. This prototype represents an efficient and effective solution to enhancing home security by leveraging modern technology.